Implementation of Natural Law and Positivism in the Recognition of Customary Law Communities in the Capital Region of the Indonesian Archipelago (IKN) - Safriansyah Yanwar Rosyadi; Yose Desman; Ade Saptomo (Warmadewa Press, 2025)
The implementation of customary law in Indonesia faces various challenges related to the recognition and protection of the rights of indigenous peoples, especially those related to customary and land rights. Although the 1945 Constitution and other regulations, such as the Forestry Law recognize the existence of indigenous peoples, the reality on the ground shows an imbalance between customary law norms and positive law, which often leads to conflict and neglect of indigenous peoples' rights. Development policies that are oriented towards economic interests frequently conflict with the traditional rights of indigenous peoples, causing injustice. This article discusses legal issues related to the implementation of customary law and provides solutions and recommendations to strengthen legal protection for indigenous people, through regulatory reform, constructive dialogue, and more inclusive development policies.